2007
DOI: 10.1007/s10592-007-9394-z
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic species diversity in a widespread bumble bee complex revealed using mitochondrial DNA RFLPs

Abstract: Cryptic species diversity is thought to be common within the class Insecta, posing problems for basic ecological and population genetic studies and conservation management. Within the temperate bumble bee (Bombus spp.) fauna, members of the subgenus Bombus sensu stricto are amongst the most abundant and widespread. However, their species diversity is controversial due to the extreme difficulty or inability morphologically to identify the majority of individuals to species. Our character-based phylogenetic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
172
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(183 citation statements)
references
References 50 publications
7
172
2
2
Order By: Relevance
“…B. magnus and B. cryptarum have been regarded as subspecies of B. lucorum and are often referred to collectively as the 'lucorum complex' or simply synonymized to B. lucorum (Benton, 2006;Edwards and Jenner, 2005). Recent studies using CO1 barcode analysis show discrete differences between the three species Murray et al, 2008;Williams et al, 2012), in accordance with studies of labial gland secretions (Bertsch et al, 2005). Diagnostic morphological characters have also been previously reported for queens, but some of these have now been demonstrated to overlap considerably, and vary along a continuum, thus making them unreliable and leading to a high potential for misidentification .…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…B. magnus and B. cryptarum have been regarded as subspecies of B. lucorum and are often referred to collectively as the 'lucorum complex' or simply synonymized to B. lucorum (Benton, 2006;Edwards and Jenner, 2005). Recent studies using CO1 barcode analysis show discrete differences between the three species Murray et al, 2008;Williams et al, 2012), in accordance with studies of labial gland secretions (Bertsch et al, 2005). Diagnostic morphological characters have also been previously reported for queens, but some of these have now been demonstrated to overlap considerably, and vary along a continuum, thus making them unreliable and leading to a high potential for misidentification .…”
Section: Introductionsupporting
confidence: 82%
“…In July 2010, 13 locations were sampled along a North-South line through the approximate centre of Scotland and England; during June-August 2011, 14 further locations were sampled focussing on the periphery of the UK. The 2011 fieldwork tested the hypothesis that B. magnus is a heathland specialist (Murray et al, 2008;Waters et al, 2010) using a paired sampling design: 11 of the 14 locations comprised a pair of sites representing heathland and non-heathland habitats within 15 km of one another. All locations sampled in 2010 consisted of non-heathland habitat, although some were close to heathland.…”
Section: Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite considerable intraspecific variation, studies based on morphology (Krüger 1958;Pekkarinen et al 1979;Rasmont 1984), cross-breeding experiments (De Jonghe and Rasmont 1983), enzyme electrophoretic data (Scholl and Obrecht 1983;Pamilo et al 1987) and analysis of the compounds of the secretion from male labial glands (Bertsch 1997) confirmed the existence of these species. Also, comparison of mtDNA sequences within the subgenus Bombus showed that species can be characterised using specific mtDNA polymorphisms (Pedersen 2002;Murray et al 2008). However, reliable identification based exclusively on morphological traits is still problematic and numerous discrepancies in classification and identification are still present.…”
Section: Introductionmentioning
confidence: 99%